2021
DOI: 10.1108/ejim-03-2021-0139
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between organizational culture and inbound open innovation

Abstract: PurposeThe relationship between corporate culture and inbound open innovation (OI) has been limited to two sub-constructs: a culture for openness and an innovation culture, but until now a richer conceptualization of corporate culture is missing.Design/methodology/approachThe authors apply Quinn and Rohrbaugh's (1983) competing values framework and regress these together with company internal and external control variables on five measures of inbound OI, reflecting product innovation, process innovation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
1
16
0
1
Order By: Relevance
“…Similarly, Naqshbandi and Tabche (2018) concluded that empowering leaders enhance open innovation by boosting organizational learning culture. Barjak and Heimsch (2023) also proved that organizational culture's rational goal and internal process model positively affect innovation inbound open process. Hence, the literature confirms that culture substantially impacts the management of open innovation in organizations (Lam et al, 2021;Qureshi et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…Similarly, Naqshbandi and Tabche (2018) concluded that empowering leaders enhance open innovation by boosting organizational learning culture. Barjak and Heimsch (2023) also proved that organizational culture's rational goal and internal process model positively affect innovation inbound open process. Hence, the literature confirms that culture substantially impacts the management of open innovation in organizations (Lam et al, 2021;Qureshi et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…The first motor theme is organizational culture and innovation, which captures topics such as innovation management, innovative work behavior, knowledge transfer, firm performance and technology transfer. This is also seen through the studies under this theme involving organizational culture is an antecedent or an important aspect of customer satisfaction (Moon and Choi, 2014), firm innovation (Uzkurt et al, 2013), innovative practices (Brandyberry, 2003), innovative work behavior (Afsar and Umrani, 2019), open innovation (Barjak and Heimsch, 2021), organizational innovativeness (Ghosh and Srivastava, 2022) and product innovation EJIM 27,3 (Valencia et al, 2010). The aspect of knowledge transfer as part of organizational culture and innovation is also noteworthy, as seen through the studies on knowledge and technology transfer (Best et al, 2016), governance of university-industry knowledge transfer (Rossi, 2010) and knowledge transfer and collaborative product development (Houman Andersen and Balslev Munksgaard, 2009).…”
Section: And Innovation Diffusionmentioning
confidence: 92%
“…The second largest basic theme is open innovation, which contain topics such as innovation performance, collaboration, and innovation process. The research under this theme appeared in 2011 and grew exponentially thereafter, ranging from open innovation adoption (Bigliardi et al, 2012;Schroll and Mild, 2011) to the determinants of open innovation (Barjak and Heimsch, 2021;Ystr€ om et al, 2015), the manifestation of open innovation in startups and SMEs (Aleksi c et al, 2022;Idrissi Fakhreddine and Castonguay, 2019;Spender et al, 2017;Usman and Vanhaverbeke, 2017), the value of collaboration (Caldas et al, 2019;Doloreux and Lord-Tarte, 2013;O'Connor et al, 2021), and the outcomes of open innovation (Franco et al, 2022;Frank et al, 2022), including innovation performance (Farzaneh et al, 2021;Lazzarotti et al, 2017;Zhong et al, 2022). The majority of research under this theme is situated in the European context and case studies appeared to be a prominent research approach to study open innovation.…”
Section: And Innovation Diffusionmentioning
confidence: 99%
“…Corporate culture has always been an important factor influencing corporate innovation. Establishing an appropriate corporate culture can improve SMEs' innovation outcomes (Barjak & Heimsch, 2023). DC refers to a set of common assumptions and understandings established by enterprises about how organizations function in a digital context (Martínez‐Caro et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%